A Case Study On Texchem Food SDN BHD’S Readiness For GST Implementation - Abdullah, Affendi; Soon, Gim Hoe; Tan, Aik Yong (2014)
With the announcement of Goods and Service Tax (GST) implemented by our government during the Budget 2014 on 25th October 2013, the current consumption tax systems of Sales Tax and Service Tax (SST) will be officially replaced with effect from 01st April 2015. The announcement has since triggered various reactions and perceptions from every level of the society, including manufacturers, accountants, logisticians, retailers, financial institutions, housing developers, general public, etc. that the price of a wider range of products and services will soon be impacted and increase inevitably.